Pembelajaran Sains Interaktif Berbasis Eksperimen dan Teknologi di SDIT Tazkia Insani Majalengka - Astuti, Tiwi Nur; Hanifah, Sarina; Puspita, Retno Ayu; Rayhansyah, Irfan Syamil; Hanin, Haya Satirah; Farindra, Muhammad Fajar Irzha (Universitas Bengkulu, 2025)
This community service aims to enhance students’ understanding and interest in science through interactive learning based on experiments and technology at SDIT Tazkia Insani Majalengka. Science education at the elementary school level is a crucial foundation for building students’ understanding and interest in natural sciences. This activity combines direct experimental methods and the use of virtual laboratories to provide a comprehensive learning experience. Students participate in experiments to deepen their understanding of scientific concepts. This approach enables students to develop observation, analysis, and problem-solving skills while utilizing modern technology. The results of the service showed an increase in students’ enthusiasm and understanding of science material. This activity aligns with the Sustainable Development Goals (SDGs) to create quality education. Keywords: Science Learning; Interactive Learning Media; Experiment;, Technology; Learning Interest